Aplikasi Fuzzy Linier Programming dengan Metode Branch and Bound untuk Mengoptimalkan Jumlah Produksi dan Keuntungan Penjualan Roti di Italia Bakery Bandar Lampung - Achmad Suryadi Nasution; Fatin Trihastuti; Sri Efrinita Irwan (Indonesian Journal of Applied Mathematics, 2023)
Italia Bakery is one of the bakeries in Bandar Lampung that produces various types of sandwiches, namely meat bread, and green bean bread. The Italian Bakery factory has difficulty in determining the optimal amount of bread production as well as controlling the right amount of raw materials. This causes losses for the factory because bread that is not worth the market will be thrown away, as a result of which the profits obtained do not reach the maximum limit. This problem can be solved by planning the optimal production amount based on the amount of raw material supply and the amount of demand with fuzzy linear programming methods. Results that have been completed with fuzzy linear programming that is still a fractional number can be rounded using the branch and bound method. Based on the results of research conducted, it is known that the use of both methods can increase the company's profits by 8,17%.